Evaluación Financiera a la Comercializadora Plasticom de la Ciudad de Zamora, Periodos 2014 – 2015 - Sandoval Mora., Karen Stefany (2016)
The development of the thesis : "Financial evaluation on PLASTICOM in Zamora, period 2014 - 2015", is framed within the parameters set by the Regulation of Academic Board of the National University of Loja , created to establish the real economic and financial position of the company and make a successful managerial assertive decision and therefore make detailed report of the findings found with the respective conclusions and valid, reasonable and appropriate recommendations that will help to improve the company. The financial structure allowed to know the participation of different industries involved in the economic and financial position of the company; performing a vertical and horizontal analysis increases and decreases were determined as well as distribution of figures in the financial statements; applying financial indicators liquidity , activity , debt, and profitability became known; economic and financial performance was analyzed through evaluation measures such as: The Economic Added Value ( EVA ) and the DUPONT System, which allowed them to propose alternatives for improvement that lead to increased profitability levels and thus achieving permanency and survival of the company; these alternatives are embodied in a Financial evaluation report that constitutes a guide for company owners regarding the appropriate decision making and the implementation of necessary corrective actions. 8 For the development of this thesis and to reach the objective knowledge of reality relying on methods and techniques that allowed to deduce, analyze and interpret situations or events that caused significant changes in activities or operations of the company; at first instance the methodology consisted in the recognition of the entity under study, aimed at finding the reference point for the formulation of the Financial Evaluation, interviews to the manager and staff of the entity were conducted, achieving credible and reliable information , in this case the financial statements, the same that were submitted to procedures from financial analysis and evaluation measures, these provided quantifiable and comparison data which made it possible to analyze the financial implications of the decisions that have been taken in the company. According to the results it was determined that the main problem of PLASTICOM is that it has not made a financial assessment from its economic initiation it is for this reason that the company is unaware for obvious reasons what their strengths, weaknesses and actions are and measures to be taken to improve their current situation. Regarding the vertical analysis, it was possible to determine that in the group of assets, in both the year 2014 and the year 2015 accounts receivable occupy most of the total of the same with 57.42% and 52, 19% respectively; In the same way, inventories of goods for sales have significant values with 30.44% in 2014 and 33.87% in 2015, since the owner has invested the greater part in merchandise because he took advantage of 9 the Advantages offered by suppliers such as discount and ease of payment and therefore in the two periods analyzed, the suppliers account accounts for most of total liabilities with 87% and 92.97%; Therefore the company's credit policies are not adequate since there is a high level of investment in accounts receivable from its customers, which are becoming uncollectible, and in this way leads to the company is less solvent To cover the obligations it has with third parties, for this reason the marketer has high indebtedness rates and is practically operating with other people's capital, in addition to that the income obtained in relation to income only represents 1.11% in 2014 and 0.32% in 2015. As for the horizontal analysis, the results showed that the asset decreased by 5.79% due to the reduction of Accounts Receivable to Shareholders, in the same way the liability decreased by 4.80% due to a significant reduction of The Obligations with Financial Institutions and Other Accounts Payable, sales increased by 6.59% as well as costs and expenses by 7.44% due to the considerable increase in Cost of Sales of $ 37,931.83, which Results in a reduction of 69.32% in relation to the year 2014, so that the company must present greater emphasis on strategies to improve its sales and reduce costs and expenses in order to obtain higher economic returns. In determining the main financial reasons, the following results were obtained: in 2014 for every dollar of debt, the company had $ 0.90 to settle it and in 2015 a value of $ 0.88, which does not represent a guarantee for creditors, Since the 10 company has problems to cancel its debts; The working capital of the marketer in 2014 was $ (31,214.07) and in 2015 ($ 38,527.89), which means that once the company cancels all its current obligations it has no capital For the normal development of their economic activities; The inventory of goods during the period 2014 rotates 4.14 times in the year is every 84 days and during the 2015 period rotates 4.31 times in the year is every 87 days, which is not efficient for the company since The inventory is sold almost quarterly; The receivables were 2.45 times during the year 2014, that is to say every 118 days and 3.05 times during the year 2015, that is to say every 147 days, therefore the marketer counts on a rotation of wallet representatively low, Which implies that the period of time of collection is extensive and therefore obtains a lower liquidity; The accounts payable were 1.45 times during the year 2014, that is to say every 248 days and 1.57 times during the year 2015, that is to say every 229 days, consequently the company must readjust its payment strategies towards its suppliers so that it can To define adequate terms that allow him to face his obligations and thus not to fall into delinquency rates or to lack the trust that his suppliers have given him; The leverage index shows that every dollar of the shareholder is committed in more than 100%, that is to say the marketer is over indebted, which generates that the profits are minimal since the net profit margin corresponded to the 0.74% of the net sales In 2014 and 0.21% in 2015, so shareholders do not obtain efficient results according to the investment they make. After completing the thesis work is recommended to increase new policies regarding the periodic application of a Financial Evaluation for the manager, the owners and staff to know the real situation of the company, seek the fulfillment of their objectives and goals and achieve proper administration based on their economic and financial situation.